Analisis Bibliometrik Tren Global Penelitian Kepemimpinan Transformasional dan Kinerja Guru - Silfiana Silfiana; Dedy Achmad Kurniady; Sururi Sururi (Universitas Negeri Malang, 2020)
Abstract: This study aims to analyze the dynamics and global trends of scientific publications on transformational leadership and teacher performance using a bibliometric approach. The main focus of this research is to map the development of studies, intellectual structure, networks of authors, institutions, countries, and dominant research themes over the last five years. The method employed is bibliometric analysis with data sourced from the Scopus database. The data were analyzed using VOSviewer software to visualize keyword networks, author collaboration, and institutional affiliations, and were further examined descriptively based on publication and citation patterns. The results indicate that publications on transformational leadership and teacher performance have increased significantly after 2020, with Indonesia emerging as the most productive contributing country. Keyword mapping shows that “transformational leadership” serves as the central node strongly connected with “teacher performance,” “motivation,” and “job satisfaction.” These findings suggest that the influence of transformational leadership on teacher performance is predominantly indirect and mediated by psychological and organizational factors. In conclusion, this study confirms that transformational leadership plays a strong, systemic, and sustainable role in enhancing teacher performance. It is recommended that future research integrate digital leadership and local cultural values, as well as apply more diverse methodological approaches, to further enrich the development of knowledge in the field of educational management. Keywords: Transformational leadership; Teacher performance; Educational management; Bibliometric analysis; Work motivation Abstrak: Penelitian ini bertujuan untuk menganalisis dinamika dan tren global publikasi ilmiah mengenai kepemimpinan transformasional dan kinerja guru melalui pendekatan bibliometrik. Fokus utama penelitian ini adalah memetakan perkembangan penelitian, struktur intelektual, jejaring penulis, institusi, negara, serta tema-tema utama yang berkembang dalam lima tahun terakhir. Metode yang digunakan adalah analisis bibliometrik dengan sumber data berasal dari basis data Scopus. Data dianalisis menggunakan perangkat lunak VOSviewer untuk memvisualisasikan jaringan kata kunci, penulis, dan afiliasi, serta dianalisis secara deskriptif berdasarkan jumlah publikasi dan sitasi. Hasil penelitian menunjukkan bahwa publikasi mengenai kepemimpinan transformasional dan kinerja guru mengalami peningkatan signifikan setelah tahun 2020, dengan Indonesia sebagai negara penyumbang publikasi terbanyak. Peta kata kunci menunjukkan bahwa “transformational leadership” merupakan simpul utama yang terhubung erat dengan “teacher performance”, “motivation”, dan “job satisfaction”. Temuan ini mengindikasikan bahwa pengaruh kepemimpinan transformasional terhadap kinerja guru bersifat tidak langsung dan dimediasi oleh faktor psikologis serta organisasi. Simpulan penelitian menegaskan bahwa kepemimpinan transformasional memiliki peran yang kuat, sistemik, dan berkelanjutan dalam meningkatkan kinerja guru. Kata kunci: Kepemimpinan transformasional; Kinerja guru; Manajemen pendidikan; Analisis bibliometrik; Motivasi Kerja